SO219A raw data of EM120 multibeam echosounder (bathymetry, beam time series & water column) - Wefer, Gerold; dos Santos Ferreira, Christian (PANGAEA, 2019)
Batyhmetry data based on the KONGSBERG Multibeam system EM120 was recorded during the RV SONNE cruise SO219A (Yokohama-Yokohama). The cruise took place between 08.03.2012 and 06.04.2012 in the Northwestern Pacific (Japan Trench) and was divided into two legs. The main research goal of the cruise was the investigation of the sedimentary fingerprint of the region caused by the 2011 Tohoku-Oki earthquake. Therefore the Remotely Operated Vehicle (ROV) QUEST (MARUM) was used to investigate fault zones and normal fault systems, which might co-seismically moved during the earthquake. Additionally slumps, seeps, and other structures , which might be related to the fault systems and therefore to the earth quake, were further explored using the ship-mounded hydroacoustic equipment (Multibeam and Parasound). CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the RV SONNE cruise SO219A the KONGSBERG EM120 multibeam echosounder with a nominal sounding frequency of 12 kHz was utilized. Up to 191 individual beams are formed for each ping. The seafloor is detected using amplitude and phase information for each beam sounding. The beams could covered a swath width of 150° across track, however due to deficient data quality the maximum swath width during the cruise was only up to 120°/130°. For further information consult https://www.km.kongsberg.com/. Responsible person during this cruise / PI: Christian dos Santos Ferreira (cferreira@marum.de) Chief Scientist: Prof. Dr. Gerold Wefer (gwefer@marum.de) CR: https://elib.suub.uni-bremen.de/edocs/00103574-1.pdf CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2012/20120100.htm, https://www2.bsh.de/aktdat/dod/fahrtergebnis/2012/20120101.htm A special thanks goes to the following watchkepper during SO219A: Sato, Takeshi, Kanamatsu, Toshiya ; Macron, Yann; Römer, Miriam; Podszun, Lina
Keywords: batyhmetry; EM120; hydroacoustic; Japan Trench; ROV; Sedimentology; SO219A